Imprensa e o enquadramento noticioso das leis de zoneamento urbano de Salvador (BA) e São Paulo (SP) - Costa, Thiago de Sousa (2019)
Public policy scheduling is often treated as one of the phases of the public policy cycle. It is at this stage that we seek to justify and convince society of the need to intervene in the social environment to solve a specific problem. A theme can be scheduled from the intentional and deliberate work of one or more stakeholders, such as government, third sector, business and media; The latter has a significant importance in scheduling, since it is still through it that the major problems of public order reach most of the population. The scheduling process, however, can often be conflicting, such as the Urban Zoning Law of the city of São Paulo (SP). Thus, the question that incites the present research is: what are the main specificities of the framing process of an urban zoning bill? The research theme, therefore, is the framing of public policies by the media. This research aims to specify the news framing processes of the zoning bills of the cities of São Paulo (SP) and Salvador (BA). For that, we used the methodology of the news framing of the generic, episodic and thematic type from a previous content analysis. To this end, the media coverage of the process of drafting, processing and approving the new zoning laws of these two cities is analyzed. As a result, it was observed that the news framework of urban zoning laws has four patterns: focus on economic issues, prevalence of conflict coverage, strong presence of formally constituted political actors, and absence of human focus on coverage.